Neoadjuvant Chemoradiotherapy and Postoperative Digestive Fistula: Neoadjuvant Chemoradiotherapy and Postoperative Digestive Fistula - Araujo-Filho, Irami; Menseses Rêgo, Amália Cinthia (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2024)
The pivotal role of neoadjuvant chemotherapy and radiotherapy in enhancing the management of gastrointestinal cancers is incontrovertible. However, their implications for surgical outcomes, particularly the risk of postoperative anastomotic fistulas, necessitate comprehensive analysis. This review examines the intricate relationship between neoadjuvant treatments and anastomotic fistula formation across a spectrum of gastrointestinal cancers, integrating findings from diverse clinical studies to elucidate risk factors and potential mitigation strategies. The timing and duration of neoadjuvant therapy emerge as critical considerations, with evidence suggesting that optimized intervals between therapy completion and surgical intervention may significantly influence fistula risk. Furthermore, patient-specific factors, including underlying health conditions and tumor characteristics, are highlighted as influential in determining fistula susceptibility. Through synthesizing current research, this review aims to guide clinical decision-making by providing insights into the balancing act of maximizing oncological efficacy while minimizing surgical complications. Future directions call for tailored treatment approaches, incorporating individual risk profiles and emerging therapeutic modalities to enhance patient outcomes in the neoadjuvant setting.